Durability of concrete bearing polymer-treated mixed recycled aggregate. (10th January 2022) - Velardo, P.; Sáez del Bosque, I.F.; Sánchez de Rojas, M.I.; De Belie, N.; Medina, C.
Graphical abstract: Highlights: Polymer-coated mixed recycled aggregates are analysed. Pre-treated MRA-bearing concrete durability is assessed. The highest performance is observed for air-dried polymer-coated MRA. MRA treatment improves concrete microstructure and lowers porosity. The new concretes are durability criteria-compliant. Abstract: The construction industry's growing interest in the use of recycled aggregate in concrete manufacture is being fuelled by an ongoing demand for more sustainable materials. The main obstacle to implementing that principle is the lower quality of recycled than natural aggregate and consequently of recycled than conventional concrete, especially with regard to durability. A number of techniques have been designed and developed of late to improve the properties of recycled aggregate. This is the first study to assess the effect of incorporating polymer pre-treated mixed recycled aggregate (MRA) on concrete durability. In this way, the properties of the concrete in terms of water transport parameters such as permeability to pressurised water, total water absorption, and capillary absorption; and of chloride penetration, air permeability, microstructure and porosity were studied. In the pre-treatment applied, the MRA was first soaked in a 20 % polymeric solution for 60 min and subsequently oven- or air-dried. The results showed similar concrete fresh state density and percentage of entrained air in the mixes studied; as well as no significant effect was found on compressive strength. However, greater durability in air- than oven-dried pre-treated MRA-bearing concrete was obtained, attested to by the 64 % lower water permeability, 17 % lower sorptivity, 58 % lower oxygen permeability, 28 % lower chloride penetration and 11 % lower total porosity in the former than observed in a reference concrete prepared with untreated recycled aggregate.